Explaining Islamist insurgencies : the case of al-Jamaah al-Islamiyyah and the radicalisation of the Poso conflict, 2000-2007 - Karnavian, M. Tito (New Jersey : Imperial College Press, 2015)
'Explaining Islamist Insurgencies explains how and why the process of Islamist radicalisation is an important step towards acts of terrorism and in the formation of terrorist organisations by focusing on Poso, a small town in Indonesia that experienced years of armed sectarian conflict between Muslim and Chrisitian communities in 2000-2007. Building on the frameworks provided by previous studies, Muhammed Tito Karnavian employs communications theory to explore the necessary precursors for the legitimising ideology, in this case Salafi-jihadism, to be effectively disseminated'--
Al-Jamaah al-Islamiyyah: from insurgency to terrorism -- Violence in Poso: from armed sectarian conflict to terrorism, 1998-2007 -- First causal factor: disaffected persons -- Second causal factor: enabling group -- Third causal factor: legitimising ideology -- The radicalisation process of Muslims in Poso -- Conclusion and policy implications.
Includes bibliographical references (pages 269-279) and index.
Keywords: Jamaah Islamiyah (Indonesia); Insurgency -- Indonesia -- Poso (Kabupaten); Radicalism -- Religious aspects -- Islam; Ethnic conflict -- Indonesia -- Poso (Kabupaten); Christianity and other religions -- Islam; Islam -- Relations -- Christianity